2015
DOI: 10.4329/wjr.v7.i8.212
|View full text |Cite
|
Sign up to set email alerts
|

Development of biodegradable radiopaque microsphere for arterial embolization-a pig study

Abstract: Our microspheres, with the unique characteristics, can be used for transcatheter arterial embolization with effects equivalent to or better than Gelfoam and Embosphere in pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Thus, various biodegradable embolic materials have been developed. In our previous study, the new biodegradable microspheres SCBRM that we developed showed promising safety and efficacy in pigs [ 19 ]. In the present feasibility study, we further explored the safety and efficacy of SCBRM in BCLC-B HCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, various biodegradable embolic materials have been developed. In our previous study, the new biodegradable microspheres SCBRM that we developed showed promising safety and efficacy in pigs [ 19 ]. In the present feasibility study, we further explored the safety and efficacy of SCBRM in BCLC-B HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The new SCBRM were constructed as previously reported [ 19 ]. SCBRM were constructed using water insoluble and biodegradable excipients, including cetyl alcohol, cholesterol, glycol monostearate, Lipiodol ® , polycaprolactone, and stearyl acid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TACE has some clear disadvantages with respect to HCC treatment; the creation of ischemic conditions at the tumor site promotes a proangiogenic response that enables the tumor to continue to thrive. Furthermore, two popular embolic materials—the DC Bead and HepaSphere—are not biodegradable, and long-term presence of DC Bead microspheres in the body may induce inflammation, thereby causing further tissue injury (Liu et al, 2015 ). In addition, the permanency of the microspheres limits the opportunity for the vessel recanalization required for repeating TACE procedures, and the drug release measured in vitro is incomplete for doxorubicin (DOX) loaded on the beads (Jordan et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…GELFOAM, a kind of nonspherical particles, is unable to precisely control the location of embolization. Besides, the recanalization time of GELFOAM is unpredictable as a temporary embolic agent [ 6 , 7 ]. In addition, Onyx is an expensive liquid embolic agent and may cause severe vasospasm if injected rapidly [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%